Corrective effects on airway epithelial function by human amniotic epithelial cells (HAEC) when treating cystic fibrosis - Kicic, Anthony; Ling, K.; Martinovich, K.; Garratt, L.; Looi, K.; Kicic-Starcevich, E.; Iosifidis, T.; Sutanto, E.; Tarran, R.; Cmielewski, P.; Donnelley, M.; Parsons, D.; et al. (2015)
Background: Cystic fibrosis (CF) remains the most common life-shortening genetic disease affecting children. The defective protein product of the affected gene, cystic fibrosis transmembrane conductance regulator (CFTR), blocks Cl - and water absorption into the airway epithelium resulting in a reduction of the air surface liquid (ASL). Reduced ASL impedes ciliary activity and reduces clearance of airway secretions contributing to an abnormal airway microenvironment that is pro-inflammatory and promotes infection. Thus, an intervention to address the basic CFTR defect has the potential to be disease modifying. One possibility may be via the utilization of stem cells. We have previously demonstrated the potential of stem cell based therapy using hAECs in lung fibrosis (Moodley Y, et al. Am J Respir Crit Care Med. 2010;182:643-51). Hence, the aim of this study was to assess the potential of hAECs to restore ion transport function to CF airway epithelial in vitro. Methods: Primary AECs were obtained from children with CF (homozygous for F508del) when attending the Princess Margaret Hospital for Children for their annual bronchoscopy and bronchoalveolar lavage and cultures established (Sutanto EN, et al. Am J Respir Cell Mol Biol. 2011;44:761-7). Co-cultures were established at ratios of 1:1, 1:10 and 1:100 of primary AEC and hAEC respectively (Cell Applications CA, USA). Air liquid interface (ALI) cultures were also set up with hAECs and primary AECs, differentiation confirmed and resulting ASL height determined. Finally, Ussing chamber and yellow fluorescent protein (YFP) halide reporter assays were used to measure resulting CFTR function. Results: Co-cultures were successfully established at ratios of 1:1, 1:10 and 1:100 of primary AEC and hAEC respectively. ALI cultures established with hAEC at a ratio of 1:1 had a significantly greater ASL height compared to matched primary AEC ALI cultures (9.5 ± 1.0μm vs 6.0 ± 0.5μm, n=6). Ussing chamber results identified that correction of ASL height was due to enhanced CFTR-induced efflux of Cl - . This was corroborated using the YFP halide reporter which illustrated an induction of normal Cl - function of CFTR at the 1:1 co-culture cell ratio. Conclusions: We provide for the first time in vitro “proof of concept” data indicating the feasibility of cell-based therapy using hAEC to treat CF. Supported by Telethon New Children’s Hospital Grant, WA.